2011
DOI: 10.1021/jz2010144
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependence of a Temperature-Induced Solid–Solid Phase Transition in Copper(I) Sulfide

Abstract: Determination of the phase diagrams for the nanocrystalline forms of materials is crucial for our understanding of nanostructures and the design of functional materials using nanoscale building blocks. The ability to study such transformations in nanomaterials with controlled shape offers further insight into transition mechanisms and the influence of particular facets. Here we present an investigation of the size-dependent, temperature-induced solid-solid phase transition in copper sulfide nanorods from low-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
128
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(149 citation statements)
references
References 43 publications
13
128
0
2
Order By: Relevance
“…The increase in intensity can be indexed to the (011) peak of the hightemperature hexagonal phase, consistent with previous work studying the thermally driven superionic phase transition in Cu 2 S (ref. 12). The large magnitude of the changes and the long-timescale recovery of the effect are consistent with the diffraction signature of the superionic phase transition in copper (I) sulphide.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The increase in intensity can be indexed to the (011) peak of the hightemperature hexagonal phase, consistent with previous work studying the thermally driven superionic phase transition in Cu 2 S (ref. 12). The large magnitude of the changes and the long-timescale recovery of the effect are consistent with the diffraction signature of the superionic phase transition in copper (I) sulphide.…”
Section: Resultssupporting
confidence: 76%
“…2b, the time-resolved measurements (black, red, orange, pink and green traces, also indicated in Fig. 2c) show decreases in intensity by more than 15%, whereas a clear peak indexed to the high-temperature phase (blue trace) increases by a similar magnitude, indicating the expected change in crystallographic symmetry 12,22 . The full threedimensional pattern may be seen in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The transition temperature of the nanoplates (∼80°C), which occurs abruptly on heating and cooling, is somewhat lower than that of bulk Cu 2 S (∼100°C). The small suppression of the phase-transition temperature observed here for Cu 2 S nanoplates is consistent with previous studies on nanomaterials (14). The corresponding crystal structures of the L-s and H-i phases are displayed schematically in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Many reports indicated that colloidal Cu 2 S NCs were prone to form as the hexagonal and cubic phase mixtures [19,31]. Herein, hexagonal phase chalcocite Cu 2 S NCs (JCPDS # 26-1116) with good purity and crystallization were synthesized successfully, as confirmed by XRD pattern and the indexed lattice spacing in Figs 1b and c. Then based on cation exchange process shown in Fig.…”
Section: Resultsmentioning
confidence: 61%